The Islamic Philosophical Perspective on Hajj Pilgrimage Management - Kamaruding, Musmuliadi; Alias, Mohd Syahmir; Abg Muis, Abg Mohd Razif; Mokhtar, Mohammad Zulfakhairi (2017)
Hajj is the fifth pillar of Islam. Every year, during the Hajj season, millions of pilgrims came from different countries and gathered in Mecca to perform Hajj.The huge numbers of pilgrims have made the management of pilgrims became too complex.The management itself is also not reasonable if it not based on the Islamic philosophical basis.In other words, the most suitable management practice in managing pilgrims in Mecca is the management from the Islamic philosophical perspectives.Therefore, this paper aims to identify and to analyse the philosophy of hajj pilgrims management from Islamic perspectives.This paper employed document research method and was analysed with content analysis method. The result found that the philosophy of hajj pilgrims management from Islamic perspective can be identified based on four elements.The first element is epistemological aspect by referring to Qur’an and hadith as the authoritative source of knowledge.Secondly, ontological aspect which assert monotheism (tawhid) as the management mould.Thirdly, axiological aspect with the application of values in management such as excellence (ihsan), trust (amanah), and justice (‘adl).Fourthly, teleological aspect which emphasizes the pleasure of Allah (mardati’Llah) as the ultimate goal of hajj pilgrims management.In conclusion, to emphasize on these four elements of Islamic philosophy in hajj pilgrims management in Mecca is important to ensure the management activities that carried out will always gain the pleasure of Allah SWT